LIBRARY INFORMATION SYSTEM AT TAMANSISWA BANJARNEGARA VOCATIONAL SCHOOL WITH BARCODE SCANNER BASED ON PHP AND MYSQL - Aprih Widayanto; Afit Muhammad Lukman; Ragil Wijianto; Vembria Rose Handayani (Jurnal Scientia, 2023)
Information technology is growing rapidly, one of the examples is the library information system. The amount of interest in reading the public makes borrowing books that are increasingly crowded on the visit by young people and adults. Both who want to borrow a book, who want to just read in the library, and who will see what books are in the library. Libraries as providers of services to users or visitors require methods of service that are fast, easy and efficient. Existing library services are still manual causing various obstacles in the provision of services, for example library staff in providing services must record new book data into a master book, for members themselves when they want to borrow a book they have to record it into the borrow books data, calculation of the amount of fines that occur when the member is late in returning books to library staff, thus to improve services to library members it is necessary to build a system to facilitate librarians in serving their members. The research method used is Research and Development (R&D). The software development process model uses the waterfall model which consists of requirements analysis, design, implementation, and testing. Then the software used for developing this library system is Macromedia Dreamweaver CC2019, MySQL Database, Php My Admin and XAMPP.